Penanganan Kasus Viral di Media Sosial oleh Humas Polri: Studi Kasus Vina Cirebon - Chandra, Fauzi Surya; Dahniel, Rycko Amelza; Turino, Harris (Brand Communication, 2025)
This study aims to analyze the communication strategies employed by the Indonesian National Police Public Relations Division (Humas Polri) in managing viral cases on social media, using the Vina Cirebon case as a focal point. Amid a crisis marked by inconsistent information, a weak sense of crisis, and delayed responses, Humas Polri faces significant challenges in rebuilding public trust. The research uses a qualitative approach through interviews and document analysis. Findings reveal that the police’s communication strategies remain largely reactive and are not yet supported by a structured crisis management system, such as the establishment of a specialized crisis team or the development of crisis risk profiles. Strengthening public relations functions with fast, consistent, and transparent communication is essential to preserve institutional legitimacy in the digital age and the post-truth era.